2007
DOI: 10.3201/eid1301.060910
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of G2P[4] and G12P[6] Rotavirus, Bangladesh

Abstract: Rotavirus strains not covered by licensed vaccines are increasing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
114
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(127 citation statements)
references
References 37 publications
10
114
3
Order By: Relevance
“…This result was consistent with the previous fi ndings on rotavirus epidemiology in Bangladesh in which its prevalence was ≈29% (11,12). Our study demonstrated 2 peaks of rotavirus infection.…”
Section: Discussionsupporting
confidence: 93%
“…This result was consistent with the previous fi ndings on rotavirus epidemiology in Bangladesh in which its prevalence was ≈29% (11,12). Our study demonstrated 2 peaks of rotavirus infection.…”
Section: Discussionsupporting
confidence: 93%
“…Although a reduction in the episodes of gastroenteritis attributable to rotaviruses was seen between 2005 and 2008, it is not clear whether the recent introduction of rotavirus testing and sampling for the current study may be a confounding factor, and only continued surveillance will allow the monitoring of this trend in the long term. [17,18,23,[37][38][39][40][41]. These fluctuations may be driven by herd immunity and the emergence of a particular genotype may reflect the buildup of a sufficiently large population of susceptible children.…”
Section: The Burden Of Rotavirus Diseasementioning
confidence: 99%
“…In the tropics, incidence exhibits less pronounced seasonal variation (16, 21), with year-round incidence and peaks during summer or fall following monsoon rains, as in Bangladesh (22,23). Despite these contrasting patterns, few correlational studies have statistically associated environmental variables with rotavirus incidence (24,25). We focus here on the monsoon season, and on flooding in particular, which is both a major environmental disturbance in Bangladesh and one of the more prominent local manifestations Significance Rotavirus is the most common cause of diarrhea among infants and children worldwide, and is still responsible for over 400,000 deaths per year, affecting mainly developing countries.…”
mentioning
confidence: 99%